Gastric cancer detection based on blood plasma surface-enhanced Raman spectroscopy excited by polarized laser light - Feng, Shangyuan; Chen, Rong; Lin, Juqiang; Pan, Jianji; Wu, Yanan; Li, Yongzeng; Chen, Jiesi; Zeng, Haishan (Biosensors & bioelectronics, 2011)
We have recently applied surface-enhanced Raman spectroscopy (SERS) for blood plasma analysis for non-invasive nasopharyngeal cancer detection and obtained good preliminary results. The aim of this study was to develop a more robust SERS spectroscopy based blood plasma analysis method for non-invasive gastric cancer detection. The effect of different laser polarizations (non-polarized, linear-polarized, right-handed circularly polarized, and left-handed circularly polarized) on blood plasma SERS spectroscopy was explored for the first time. Silver nanoparticles as the SERS-substrate were directly mixed with blood plasma to enhance the Raman scattering of various biomolecular constituents. High quality SERS spectra were obtained using a fiber optic probe and a dispersive type near infrared Raman system. Blood plasma samples from gastric cancer patients ( n = 32) and healthy subjects ( n = 33) were analyzed. The diagnostic performance for differentiating gastric cancer plasma from normal plasma was evaluated. Principal component analysis combined with linear discriminant analysis (LDA) of the obtained spectral data was used to develop diagnostic algorithms. Classification results obtained from cross-validation of the LDA model based on the four spectral data sets of different laser polarizations demonstrated different diagnostic sensitivities and specificities: 71.9% and 72.7% for non-polarized laser excitation, 75% and 87.9% for linear-polarized laser excitation, 81.3% and 78.8% for right-handed circularly polarized laser excitation, 100% and 97% for left-handed circularly polarized laser excitation. The results from this exploratory study demonstrated that plasma SERS spectroscopy with left-handed circularly polarized laser excitation has great promise of becoming a clinically useful diagnostic tool for non-invasive gastric cancer detection.